New Technologies for Influenza Vaccines - Steven Rockman (Microorganisms, 2020)
Vaccine development has been hampered by the long lead times and the high cost required to reach the market. The 2020 pandemic, caused by a new coronavirus (SARS-CoV-2) that was first reported in late 2019, has seen unprecedented rapid activity to generate a vaccine, which belies the traditional vaccine development cycle. Critically, much of this progress has been leveraged off existing technologies, many of which had their beginnings in influenza vaccine development. This commentary outlines the most promising of the next generation of non-egg-based influenza vaccines including new manufacturing platforms, structure-based antigen design/computational biology, protein-based vaccines including recombinant technologies, nanoparticles, gene- and vector-based technologies, as well as an update on activities around a universal influenza vaccine.